PERAN CORPORATE GOVERNANCE DAN KARAKTERISTIK MANAJER DALAM MANAJEMEN LABA - SEPTIVIANI BHAYANGKARI; LAILAH FUJIANTI; TRI ASTUTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
This research with an objective to verify the correlations between corporate governance, manager characteristics and company size to the profit. The corporate governance which includes board of commissioners, audit committee and board of directors. Whereas manager characteristics that's being used is managerial educations. The number of samples that's in use are 14 industrial and chemical companies which shares are registered in Bursa Efek Indonesia in the period of 2015-2017. Based on the research results, shows that the board of commissioners variable is significantly effecting the profit managements. This proves that board commissioners are adequate to subdue the actions of earnings management. While audit committee, board of commissioners, managerial educations and company size to the profit doesn't show same significant effects to earnings management as board commissioners does.